The Association between Trading Recommendations and Broker‐Analysts’ Earnings Forecasts - Eames, Michael; Glover, Steven M.; Kennedy, Jane (Journal of Accounting Research, 2002)
This study examines analyst forecast errors within the context of stock recommendations. We predict positive forecast error (i.e., optimism) for buy recommendations and negative forecast error (i.e., pessimism) for sell recommendations. We offer two explanations for this prediction: (1) the unconscious tendency to process information in a manner that supports one’s goal, which we refer to as the “objectivity illusion” hypothesis, and (2) the economic incentive to boost trade, which we refer to as the “trade boosting” hypothesis. The pattern of analyst forecast bias we predict (i.e., optimism for buys and pessimism for sells) is opposite in direction to that predicted by the management relations hypothesis—a commonly cited hypothesis for analyst forecast bias. We find broker‐analyst earnings forecast errors are significantly optimistic for buy recommendations and significantly pessimistic for sell recommendations, consistent with the objectivity illusion and trade boosting hypotheses. Our study indicates that the pattern of results reported in prior research (i.e., increasingly optimistic earnings forecasts as the stock recommendation becomes less favorable) is likely driven by a correlated omitted variable, actual earnings. Results of an analysis to distinguish between trade boosting and objectivity illusion appear more consistent with the objectivity illusion.